(untitled) (World Bulletin of Management and Law, 2022)
The term mental accounting is one of the most used modern accounting terms in the financial decision-making process for consumers, and despite the widespread use of mental accounting among different consumers, there is still a gap in the understanding of mental accounting; That is why this study provides a framework for understanding some of the foundations upon which mental accounting is based. This study also provides a general description of the concept of mental accounting; In addition, this study discusses the various negative effects directly related to the use of mental accounting, which the decision maker is exposed to when making the outsourcing decision; Therefore, this research focused on studying the relationship between rationalizing the negative effects of mental accounting in the process of making the outsourcing decision and increasing its effectiveness. This study presented a suggested approach to rationalize these negative effects in order to increase the effectiveness of the outsourcing decision. The study suggested that rationalizing the negative effects of mental accounting in the process of making the outsourcing decision is expected to affect the increase in the effectiveness of this decision.